2012
DOI: 10.1111/j.1443-1661.2012.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective Training System in Colorectal Endoscopic Submucosal Dissection

Abstract: Although colorectal endoscopic submucosal dissection (ESD) is superior to endoscopic mucosal resection (EMR) in en bloc resection rate, it is technically quite difficult because of the anatomical and histological characteristics of the colorectal wall. This difficulty prevents wide spread of the technique. Establishment of the training system for colorectal ESD is necessary to standardize training and to achieve wider acceptance of this technique. Herein, we describe our training system for colorectal ESD, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 23 publications
1
47
0
Order By: Relevance
“…Hotta et al [21] suggested that about 40 treatments must be performed to achieve a perforation rate of less than 5%, whereas about 80 treatments must be performed to achieve proficiency, defined as reduced procedure time and good resection results. However, Sakamoto et al [22] and Ohata et al [23] showed that 30 ESD treatments performed independently in the colon were sufficient to obtain an acceptable R0 resection rate, procedure duration, and complication rate. This learning curve was confirmed by studies showing that during the first 25 treatments, the perforation rates were 12-28% [24][25][26][27].…”
Section: Discussionmentioning
confidence: 98%
“…Hotta et al [21] suggested that about 40 treatments must be performed to achieve a perforation rate of less than 5%, whereas about 80 treatments must be performed to achieve proficiency, defined as reduced procedure time and good resection results. However, Sakamoto et al [22] and Ohata et al [23] showed that 30 ESD treatments performed independently in the colon were sufficient to obtain an acceptable R0 resection rate, procedure duration, and complication rate. This learning curve was confirmed by studies showing that during the first 25 treatments, the perforation rates were 12-28% [24][25][26][27].…”
Section: Discussionmentioning
confidence: 98%
“…If the cases were assisted by experts during the trainee's performance of the procedure, it might affect clinical outcomes favorably. 18 Second, different endoscopic equipment for ESD was used in each study. A former Japanese study used a pediatric-type colonoscope (PCF-Q260JI; Olympus Optical Co.) with a built-in water jet system and a carbon dioxide insufflation system while we used a conventional colonoscope with an air insufflation system.…”
Section: Discussionmentioning
confidence: 99%
“…R0 resection was defined as an en-bloc resection without tumor involvement to the lateral and vertical margins of the resected specimen in a pathologic diagnosis. 18 We used the proficiency that was calculated as the procedure time per specimen area (min/cm 2 ). 19 Complications related to ESD procedures such as perforation and…”
Section: Assessment Of Learning Curvementioning
confidence: 99%
“…Despite greater risks of postoperative complications, particularly, more and more endoscopists are making an effort to study this new technique in terms of its capability of larger neoplasms resection, higher en-bloc resection rate and lower local recurrence rate of neoplasms in comparison with other endoscopic treatments. Ohata et al [56] proposed a 7-step training system for learning colorectal ESD, which is very similar to the training algorithms used for gastric ESD, but with the emphasis on technical differences imposed by performing the procedure in a narrower space with thinner wall. One of the mandatory enrolment criteria was performance of at least 30 gastric ESDs.…”
Section: Learning Curve For Gastric Esdmentioning
confidence: 99%
“…The study found that, regardless of the gastric ESD experience, the mean procedure time of each trainee became less than 80 min after performing more than 30 cases. Trainees with experience in many (i.e., 200) gastric ESDs could perform colorectal ESD skillfully from the initial period of training onward [56] .…”
Section: Learning Curve For Gastric Esdmentioning
confidence: 99%